Association of Risk Factors and Inflammatory Bowel Disease: a Case Control Study in a Tertiary Level Hospital - Newaz, Abdullah Al Shah; Niaz, Maj Md Kaisar; Arafat, Md Yasir; Ahmed, Farid; Raha, Arunangshu; Islam, Susmita; Islam, K M Shaiful; Islam, Susmita; Chowdhury, Md Fazlul Karim (Bangladesh Medical Journal, 2023)
The rising incidence of inflammatory bowel disease (IBD) in Bangladesh supports the importance of various risk factors in disease etiology. This case-control study aims to measure association of IBD among the patients who were exposed to various risk factors. The study was conducted in patients with IBD and a control group without IBD in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh during the period of March 2016 to January 2018. Diagnosed IBD patients aged more than eighteen years admitted or visiting for follow up in the Department of Gastroenterology were selected as cases. Controls were selected from patient’s attendants other than IBD, where age and sex were matched with cases. Controls were non-relative to the cases in the same department, and free from any bowel symptoms. Data were collected by using pre-tested questionnaire and then analyzed. Total 164 participants were selected among them 82 cases and 82 controls. Among the cases, 38 patients were diagnosed as ulcerative colitis and 44 patients were diagnosed as Crohn’s disease. Study found that ulcerative colitis were associated with the following factors namely being smoker (OR 20.31; 95% CI 2.39-172), exposure to pets (OR 11.24; 95% CI 1.86-67.76), not drinking boiling water (OR 7.33; 95%CI 1.62-33.05), bathing in open water such as river and ponds (OR 5.04; 95% CI 1.04-24.40), walking bare footed in grounds and toilet (OR 10.49; 95% CI 2.08-52.78), taking street food (OR 5.17; 95% CI1.15-23.28) and soft drinks (OR 11.55; 95% CI 0.24-9.48), where high odds ratios (OR) were measures. On the other hand, crohn’s disease were associated with the factors of being smoker (OR 10.30; 95%CI 1.15-91.9), exposure to pets (OR 19.19; 95% CI 1.74-211), not drinking boiling water (OR 10.33; 95% CI 2.54-43.51), bathing in open water such as river and ponds (OR 6.48;95% CI 1.35-31.09), consuming unpasteurized milk (OR 8.50; 95% CI 1.71-42.10) and soft drinks (OR 42.74; 95% CI 5.56-328). This study determined the risk factors of IBD in the ground of childhood behavior, hygienic condition and dietary habit for the development of IBD. Bangladesh Med J. 2022 May; 51(2): 1-12